Crime Investigation of Trade of The Human Body Organs on Criminal Investigation Police (Case Study Police Report Number: LP / 43 / I / 2016 / Bareskrim dated 13 January 2016) - Yeremias Tony Putrawan; Jawade Hafidz; Aryani Witasari (Jurnal Daulat Hukum, 2019)
The purpose of this research know and analyze doubt enforcing the investigation of criminal trafficking of human organs carried out by the Criminal Investigation Police, to determine the factors that affect the implementation of the investigation of criminal trafficking of human organs carried out by the Criminal Investigation Police, to know the efforts the police in tackling the trade in human organs and factors inhibiting the Police in tackling trafficking in human organs.The method used is the method of normative and juridical sociologic, the specifications in the study was a descriptive analytical methods of population and sampling are all objects or all of the symptoms or the entire event or the entire unit to be studied, data collection techniques using literature study and interviews, data analysis is qualitative.Result: Implementation of the investigation of criminal trafficking of human organs in accordance with the Regulation no. 14 Of 2012 on Management Investigations. In the process, the investigator did not experience any problems in the arrest of the perpetrators, because in the process of investigation the investigator obtain complete information from the victim as well as by using techniques evident triangle obtained further evidence used to ensnare offenders. The factors that affect the implementation of the criminal investigation of organ trafficking the human body that carried out by the Police Criminal Investigation divided into two: a supporting factor comes from: the power of law enforcement officers who have sufficient personnel and high professionalism, Police efforts to combat trafficking in organs, namely prevention, eradication and prevention of the crime of trafficking of human organs by running strategy repressive functions, namely in the form of punishment with the most severe penalties. Factors inhibiting factor is the legal, law enforcement, means infrastructures, society and cultureKey words: Investigation; Crime; Trafficking; Human Organs.